Dance Movement Therapy for Clients With a Personality Disorder: A Systematic Review and Thematic Synthesis - Kleinlooh, S. T.; Samaritter, R. A.; van Rijn, R. M.; Kuipers, G.; Stubbe, J. H (Frontiers in Psychology, 2021)
Background: People with a personality disorder (PD) suffer from enduring inflexible patterns in cognitions and emotions, leading to significant subjective distress, affecting both self and interpersonal functioning. In clinical practice, Dance Movement Therapy (DMT) is provided to clients with a PD, and although research continuously confirms the value of DMT for many populations, to date, there is very limited information available on DMT and PD. For this study, a systematic literature review on DMT and PD was conducted to identify the content of the described DMT interventions and the main treatment themes to focus upon in DMT for PD. Methods: A systematic search was conducted across the following databases: EMBASE, MEDLINE, PubMed, WEB OF SCIENCE, PsycINFO/OVID, and SCOPUS following the PRISMA guidelines. The Critical Appraisal Skills Programme for qualitative studies was used to rank the quality of the articles. The Oxford Center for Evidence-based Medicine standards were applied to determine the hierarchical level of best evidence. Quantitative content analysis was used to identify the intervention components: intended therapeutic goals, therapeutic activities leading to these goals, and suggested therapeutic effects following from these activities. A thematic synthesis approach was applied to analyze and formulate overarching themes. Results: Among 421 extracted articles, four expert opinions met the inclusion criteria. Six overarching themes were found for DMT interventions for PD: self-regulation, interpersonal relationships, integration of self, processing experiences, cognition, and expression and symbolization in movement/dance. No systematic descriptions of DMT interventions for PD were identified. A full series of intervention components could be synthesized for the themes of self-regulation, interpersonal relationships, and cognition. The use of body-oriented approaches and cognitive strategies was in favor of dance-informed approaches. Conclusions: Dance movement therapists working with PD clients focus in their interventions on body-related experiences, non-verbal interpersonal relationships, and to a lesser extent, cognitive functioning. A methodological line for all intervention components was synthesized for the themes of self-regulation, interpersonal relationships, and cognition, of importance for developing systematic intervention descriptions. Future research could focus on practitioners' expertise in applying DMT interventions for PD to develop systematic intervention descriptions and explore the suitability of the identified themes for clinical application. Clients' experiences could offer essential insights on how DMT interventions could address PD pathology and specific PD categories.